2013
DOI: 10.2217/pgs.13.31
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Variation in the MAP3K5 Gene is Associated with β-Thalassemia Disease Severity and Hydroxyurea Treatment Efficacy

Abstract: Our data suggest that these MAP3K5 variants are indicative of β-thalassemia disease severity and response to HU treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
1
13
0
9
Order By: Relevance
“…SCD/β-thalassemia compound heterozygous patients were systematically administered HU and characterized as “HU-responders” (plateau HbF levels above 20%) or “HU non-responders” (plateau HbF levels below 20%), based on their HbF expression levels following drug administration. All molecular, hematological, and clinical data of patient cohorts have been described in our previously published work [ 7 , 15 , 17 , 32 , 33 , 40 ]. All tagSNP genotyping samples are of Hellenic origin, collected at the Patras University Hospital (Patras, Greece), AHEPA University Hospital (Thessaloniki, Greece), and Ippokrateio General Hospital of Thessaloniki (Thessaloniki, Greece).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SCD/β-thalassemia compound heterozygous patients were systematically administered HU and characterized as “HU-responders” (plateau HbF levels above 20%) or “HU non-responders” (plateau HbF levels below 20%), based on their HbF expression levels following drug administration. All molecular, hematological, and clinical data of patient cohorts have been described in our previously published work [ 7 , 15 , 17 , 32 , 33 , 40 ]. All tagSNP genotyping samples are of Hellenic origin, collected at the Patras University Hospital (Patras, Greece), AHEPA University Hospital (Thessaloniki, Greece), and Ippokrateio General Hospital of Thessaloniki (Thessaloniki, Greece).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that genomic variants in the MAP3K5 , KLF10 , SIN3A , NOS1 , ARG1 , and ARG2 genes are associated with elevated HbF levels and, hence, milder disease severity in β-type hemoglobinopathy patients and HU treatment response rate in SCD/β-thalassemia compound heterozygous patients [ 4 , 7 , 17 , 40 ]. Herein, we adopted a whole transcriptome analysis of erythroid cells derived from human hematopoietic tissues of various developmental stages to identify candidate genes that are differentially expressed at various developmental stages.…”
Section: Introductionmentioning
confidence: 99%
“…The very low values of Hb A and Hb F in our patient suggested that they might be more susceptible to sickle cell crisis. Genetic markers that affect the level of HbF in Greek origin patients with Hb S/ β + thal should be studied [10]. …”
Section: Discussionmentioning
confidence: 99%
“…These include phosphodiesterase 7 (PDE7B), mitogen-activated protein kinase kinase kinase 5 (MAP3K5), and peroxisomal biogeneses factor 7 (PEX7) genes with their SNPs showing strong association with different HbF levels [48]. It was shown that a short tandem repeat in the MAP3K5 promoter, as well as intronic variations within both MAP3K5 and PDE7B genes could be associated with lower HbF levels and thus, more severe β-thalassemia phenotype [49]. MAP3K5, encoded by MAP3K5 gene, is a member of the MAPK family and, as such, a part of the MAPK pathway.…”
Section: Hbs1l-myb Intragenic Regionmentioning
confidence: 99%